Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) untuk Meningkatkan Keaktifan Belajar Pendidikan Pancasila Siswa Kelas V UPTD SD Negeri 71 Parepare - Ritha Tuken; Ila Israwaty; Nur Fitrah (MASALIQ, 2026)
Low student engagement in Pancasila Education learning affects students’ emotional and cognitive involvement in elementary school. This study aims to analyze the process and outcomes of implementing the Think Pair Share (TPS) cooperative learning model to improve the learning engagement of fifth-grade students at UPTD SDN 71 Parepare. The study employed a Classroom Action Research design conducted in three cycles involving 42 students selected through purposive sampling. Data were collected through observation sheets and documentation and then analyzed using qualitative descriptive techniques. The results showed that students’ learning engagement gradually increased from the low category in Cycle I, with a percentage of 34.37%, to the moderate category in Cycle II, at 46.87%, and reached the high category in Cycle III, at 68.75%. These findings indicate that the structured implementation of the TPS model can improve the quality of the learning process and student engagement in Pancasila Education learning. This study strengthens the application of cooperative learning theory, particularly a learning structure that promotes individual activity, paired interaction, and participation in classroom discussions. Practically, the findings can serve as a reference for elementary school teachers in developing more interactive and participatory Pancasila Education learning. Future research may examine the role of individual accountability in implementing cooperative learning in classes with large numbers of students.